2019
DOI: 10.5603/fm.a2018.0114
|View full text |Cite
|
Sign up to set email alerts
|

Sex and level differences in the diameters of extradural segment of vertebral artery: computed tomography angiographic study

Abstract: Background: We investigated diameters of prevertebral-V1, and atlantic-V3 parts of extradural segment of vertebral artery (VA). Variable results from the literature about VA diameters reflect variety of diagnostic and imaging methods, various sample sizes, different levels of measurements, and lack of possible specific ethnic, regional or genetic data. Additionally, the data are often without distinctions of left-right or of sex. Materials and methods: For this computed tomography (CT) angiographic study 91 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…For investigated atlantic (V3) part of VA, the mean diameters found in our previous study [30] for RVA (males 3.27 mm; females 2.88 mm) and for LVA (males 3.39 mm; females 3.01 mm), were practically identical as in current study, because the sample population was same, with the exclusion of few patients having ICA abnormalities. In previous studies [30,33], also were found in males larger diameters highly significantly of LVA and significantly of RVA, but not significant intrasex left-right differences. Because of the high interindividual variability, the normal range for diameter, peak systolic velocity and VA blood flow is wide in both VAs [24].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For investigated atlantic (V3) part of VA, the mean diameters found in our previous study [30] for RVA (males 3.27 mm; females 2.88 mm) and for LVA (males 3.39 mm; females 3.01 mm), were practically identical as in current study, because the sample population was same, with the exclusion of few patients having ICA abnormalities. In previous studies [30,33], also were found in males larger diameters highly significantly of LVA and significantly of RVA, but not significant intrasex left-right differences. Because of the high interindividual variability, the normal range for diameter, peak systolic velocity and VA blood flow is wide in both VAs [24].…”
Section: Discussionsupporting
confidence: 82%
“…1). Diameters of VA were measured at atlantic (V3) segment of VA (5 mm before entrance into dural porion of VA), in order to exclude the potential influence of variable collateral branches anatomy from V2 segment [30].…”
Section: Methodsmentioning
confidence: 99%
“…CTA has been frequently in imaging examinations to simultaneously reveal the three-dimensional anatomy surrounding V3, as it has the advantages of being noninvasive and fast and yielding volumetric scans. Morphometric analyses of V3 performed by using CTA have been reported in many studies (19)(20)(21)(22)(23)(24), but the branches of V3 have been studied in few studies, with small sample sizes of cadavers due to the high cost and intricate procedures required (25)(26)(27). Although a large sample of vertebral arteries can be assessed by CTA, the branches of V3 have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%